Urban slums in security housing in China - Zhang, Tao; Hashim, Ahmad Hariza; Jawan, Jayum (David Publishing Company, 2011)
As wealth gap is widening and the housing price increases tremendously in China, the living standard of urban underclass maintains relatively low level. Therefore, possessing a house is becoming more difficult than ever for those urban poor strata. Consequently, the poor are forced to settle in damp and congested substandard housing where plagues, crimes and relegation of social regulations and morality are incidental with. Security housing system has been established in China, and its purport is to alleviate the housing plight of urban poor people. But in reality, security housing is becoming a new form of urban slum. This paper aims to investigate the causes of this phenomenon and provide some recommendations. In addition, this paper attempts to identify the characteristics of current security housing situation and to interpret the right to housing.